2019
DOI: 10.1093/neuros/nyz347
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Occurrence of Postoperative Distal Junctional Kyphosis in Cervical Deformity Patients

Abstract: BACKGROUND Distal junctional kyphosis (DJK) development after cervical deformity (CD)-corrective surgery is a growing concern for surgeons and patients. Few studies have investigated risk factors that predict the occurrence of DJK. OBJECTIVE To predict DJK development after CD surgery using predictive modeling. METHODS CD criteria was at least one of the foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(58 citation statements)
references
References 25 publications
3
45
0
3
Order By: Relevance
“…Passias et al have also determined that the following surgical factors are associated with DJK risk: combined approach, posterior upper instrumented vertebrae below C4, use of transition rod, lack of anterior corpectomy, more than three posterior osteotomies, and performance of a 3-column osteotomy. 24…”
Section: Discussionmentioning
confidence: 99%
“…Passias et al have also determined that the following surgical factors are associated with DJK risk: combined approach, posterior upper instrumented vertebrae below C4, use of transition rod, lack of anterior corpectomy, more than three posterior osteotomies, and performance of a 3-column osteotomy. 24…”
Section: Discussionmentioning
confidence: 99%
“…Various techniques of ventral and dorsal approaches to the adult cervical spine have been described [3, 10, 13-15, 32, 33, 40]. In a recent review by the International Spine Study Group, 13 sites with adult cases were studied to predict the occurrence of postoperative distal junctional kyphosis in cervical deformity patients who underwent surgical procedures [28]. There was a 23.1% prevalence of distal junctional kyphosis in 117 adult patients with cervical deformity.…”
Section: Discussionmentioning
confidence: 99%
“…No long-term pediatric results are available. Recent review articles and meta-analysis in adults have been made in an effort to better understand cervical deformity, but the weakness is a crossstudy analysis, differences in outcome measures, and surgical approach [3,10,11,18,28,37]. The deformity may result from posterior cervical instability from laminectomy as well as trauma.…”
Section: Introductionmentioning
confidence: 99%
“…DJK has been defined as a loss of radiographic alignment at one or two levels distal to the lowermost instrumented vertebra (LIV) and is associated with adjacent level failure, instrumentation failure, and spondylolisthesis. 62 A study by Passias and colleagues demonstrated a 1-yeay postoperative rate of 23.1% for DJK. 62 DJK occurred most commonly at 3 months postoperative and patients with DJK had significantly more severe cervical malalignment at baseline, as measured by T1S-CL, CL, cSVA, C2-T3 angle, and C2 slope.…”
Section: Surgical Complicationsmentioning
confidence: 99%
“…62 A study by Passias and colleagues demonstrated a 1-yeay postoperative rate of 23.1% for DJK. 62 DJK occurred most commonly at 3 months postoperative and patients with DJK had significantly more severe cervical malalignment at baseline, as measured by T1S-CL, CL, cSVA, C2-T3 angle, and C2 slope. 62 Since DJK is a critical complication of cervical deformity correction, there are a few DJK prevention methods that include the use of medications to strengthen bone density such as teriparatide, appropriate selection of the LIV in relation to the curve apex, and ligament augmentation.…”
Section: Surgical Complicationsmentioning
confidence: 99%